Praznovanje 400-letnice reformacije v Ljubljani leta 1917 v luči arhivskih virov ter slovenskega in nemškega tiska - Žigon, Tanja (Stati inu obstati, 2018)
In view of the celebrations of the 500th anniversary of the Reformation, which was marked in 2017, this paper reflects on how the anniversary of the Reformation was remembered a hundred years ago in Carniola and especially in Ljubljana. Since the Evangelical religious municipality in Ljubljana was small and considering that in 1917 a war was raging in the hinterland, there probably were no particular reasons for a big celebration. The question arises whether the anniversary was marked at all in Ljubljana, and if it was, how and what ceremonies were organized. Based on the records and reports from the legacy of the Evangelical church community in Ljubljana, as well as on the rare mentions in the newspapers of the time, which were published either in German or in Slovene, the paper will reconstruct the events that took place in Ljubljana in that period.
Keywords: 1917; anniversary of the Reformation; archival material; arhivsko gradivo; časopisi; Evangelical religious municipality in Ljubljana; evangeličanska cerkvena občina; Ljubljana; newspapers; obletnica reformacije; Ottmar Hegemann